Photocatalytic performance and mechanism of hydrogen evolution from water over ZnCdS/Co@CoO in sacrificial agent-free system. (15th July 2022) - Zou, Yangyang; Guo, Changyan; Cao, Xianglei; Chen, Tingxiang; Kou, Yuli; Zhang, Liugen; Wang, Tao; Akram, Naeem; Wang, Jide
Abstract: Photocatalytic efficient hydrogen evolution from pure water with non-noble metal system has more practical application value. In this study, the ZnCdS/Co@CoO composite photocatalyst was prepared by a simple hydrothermal reduction method. The hydrogen evolution rate from water can reach to 793 μmol·g −1 ·h −1 in sacrificial agent-free system, and 5445 μmol·g −1 ·h −1 with Na2 S and Na2 SO3 as sacrificial agent. The S-scheme heterojunction formed between ZnCdS and Co@CoO, as well as the abundant S vacancy were proved to be the key factors to effectively improve the photocatalytic performance. The study on the high hydrogen production efficiency and catalytic mechanism of ZnCdS/Co@CoO in sacrificial agent-free can provide ideas for the design and preparation of more efficient non-noble metal photocatalysts. Graphical abstract: Image 1 Highlights: The tiny ZnCdS/Co@CoO nanoparticles effectively shorten the electron transport distance. The hydrogen yield can reach 793 μmol g −1  h −1 in sacrificial agent-free system. The S vacancy acts as electron trap and avoids the recombination of electrons and holes. The S-scheme heterojunction can be constructed between ZnCdS and Co@CoO. The S-scheme heterojunction is favorable for the separation and transfer of electron-hole pair.